Knowledge of Mothers on Factors Associated with Anaemia among Children under Five Years Old in Orile-Agege General Hospital, Lagos, Nigeria - Ajala, Josephine Oyebimpe; Ojerinde, Abosede Catherine (International Journal of Child Health and Nutrition, 2015)
Anaemia in children under five years old is a public health concern worldwide. In developing countries about 12 million children under five years old die each year from preventable causes. The deaths of over 6 million are either directly or indirectly attributed to malnutrition, mainly under-nutrition that leads to anaemia and constitutes a high percentage of infant and child mortality. This descriptive survey attempted to assess the knowledge of mothers on factors associated with anaemia among children under five years old in the child welfare clinic at Orile-Agege General Hospital, Lagos. The 120 respondents were conveniently selected and data was collected through a close ended question items and analyzed with Pearson Product Moment Correlation. The findings revealed that 111(92.5%) of the respondents agreed that one of the major causes of anaemia was malnutrition. Consequently, respondents agreed that children who suffer from anaemia are prone to infections, delayed psychomotor development, poor academic performance and low scores in intelligent (IQ) tests which deprived them the opportunity to be physically fit and function at optimal level. There was no significant relationship between occurrence of anaemia and mothers’ educational status (r = .29) as well as their socio economic status (r = .091). The religious belief of the respondents also had no bearing with the occurrence of anaemia (r =.152). It was therefore recommended that there is need for more public enlightenment on the causes, prevention and complications of anaemia. Capacity building for health care providers to adequately equip them with updates and facts on the management of prevailing rate of anaemia effectively. Anaemia in children under five years old is a public health concern worldwide. In developing countries about 12 million children under five years old die each year from preventable causes. The deaths of over 6 million are either directly or indirectly attributed to malnutrition, mainly under-nutrition that leads to anaemia and constitutes a high percentage of infant and child mortality. This descriptive survey attempted to assess the knowledge of mothers on factors associated with anaemia among children under five years old in the child welfare clinic at Orile-Agege General Hospital, Lagos. The 120 respondents were conveniently selected and data was collected through a close ended question items and analyzed with Pearson Product Moment Correlation. The findings revealed that 111(92.5%) of the respondents agreed that one of the major causes of anaemia was malnutrition. Consequently, respondents agreed that children who suffer from anaemia are prone to infections, delayed psychomotor development, poor academic performance and low scores in intelligent (IQ) tests which deprived them the opportunity to be physically fit and function at optimal level. There was no significant relationship between occurrence of anaemia and mothers’ educational status (r = .29) as well as their socio economic status (r = .091). The religious belief of the respondents also had no bearing with the occurrence of anaemia (r =.152). It was therefore recommended that there is need for more public enlightenment on the causes, prevention and complications of anaemia. Capacity building for health care providers to adequately equip them with updates and facts on the management of prevailing rate of anaemia effectively.